2007
DOI: 10.1002/bsl.778
|View full text |Cite
|
Sign up to set email alerts
|

When is profiling possible? Offense planning and aggression as moderators in predicting offender age from victim age in stranger rape

Abstract: Debate continues with regard to the possibility of inferring an offender's characteristic features from crime scene details (the process of so-called "offender profiling"). We argue that psychology generally has benefited from appreciating context in predicting behavior. In the same way, profiling would benefit from an appreciation of context in predicting characteristics. This "reverse" process is contingent on various "if...then" relationships. As one example, this paper demonstrates how profiling offender a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 46 publications
2
47
1
2
Order By: Relevance
“…We were careful to investigate the predictive ability of variables under the multivariate approach in relation to one another by using full logistic models; however, the extrapolation of single significant predictors is inevitable. Goodwill and Alison (2007) recently illustrated that bivariate relationships between crime scene information and offender characteristics can be dependent on the presence or absence of other behavioral, contextual, or situational aspects. Accordingly, Goodwill and Alison (2007) further suggest that the relationship between crime scene information and offender characteristics is likely to be a multifaceted one and interdependent with what other behavioral, contextual, or situational factors are present.…”
Section: Impact Of Methodological Differences In the Prediction Of Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…We were careful to investigate the predictive ability of variables under the multivariate approach in relation to one another by using full logistic models; however, the extrapolation of single significant predictors is inevitable. Goodwill and Alison (2007) recently illustrated that bivariate relationships between crime scene information and offender characteristics can be dependent on the presence or absence of other behavioral, contextual, or situational aspects. Accordingly, Goodwill and Alison (2007) further suggest that the relationship between crime scene information and offender characteristics is likely to be a multifaceted one and interdependent with what other behavioral, contextual, or situational factors are present.…”
Section: Impact Of Methodological Differences In the Prediction Of Ofmentioning
confidence: 99%
“…Goodwill and Alison (2007) recently illustrated that bivariate relationships between crime scene information and offender characteristics can be dependent on the presence or absence of other behavioral, contextual, or situational aspects. Accordingly, Goodwill and Alison (2007) further suggest that the relationship between crime scene information and offender characteristics is likely to be a multifaceted one and interdependent with what other behavioral, contextual, or situational factors are present. This point, circularly, is in fact the premise for the investigation and adoption of thematic and typological approaches: to account for the often found interdependence of behavior and situational complexity.…”
Section: Impact Of Methodological Differences In the Prediction Of Ofmentioning
confidence: 99%
“…Other attempts at linking offense characteristics to sex offender characteristics have used either some forms of multidimensional scaling (Canter et al, 2003;Häkkänen, Lindlöf, & Santtila, 2004;Kocsis, Cooksey, & Irwin, 2002) or regression analyses (e.g. Beauregard, Lussier, & Proulx, 2007a;Goodwill & Alison, 2007;Scott et al, 2006). In this issue, ter Beek, van den Eshof, and Mali used logistic regression on a sample of 271 stranger rape offenses included in the ViCLAS database of The Netherlands, and found that crime characteristics can be used to 'profi le' offender characteristics, thus providing further weight to the A → C equations.…”
Section: The a → C Equationsmentioning
confidence: 99%
“…O perfil psicológico para identificar criminosos sexuais, embora utilizado por alguns pesquisadores, ainda requer melhor validação científica, visto que seus procedimentos são em sua maioria decorrentes de pesquisas empíricas 43 . Diante do quadro exposto, todavia, tal prática é muitas vezes necessária na esfera da psiquiatria e da psicologia forense, não só como forma de ampliação do conhecimento da dinâmica do indivíduo agressor, mas também contribuindo para a determinação da sua capacidade de entendimento e autocontrole.…”
Section: Considerações Finaisunclassified